2011
DOI: 10.1097/mpg.0b013e31821cf503
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Specific Foods Responsible for Inflammation in Children With Eosinophilic Esophagitis Successfully Treated With Empiric Elimination Diet

Abstract: Serial single-food reintroductions following induction of histological remission with the SFED can lead to the identification of specific causal food antigen(s) in EoE. Cow's milk was the most common food identified in subjects with EoE treated with SFED. A subset of children with EoE may develop tolerance to their food sensitivities while on the SFED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
177
5
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(193 citation statements)
references
References 21 publications
4
177
5
7
Order By: Relevance
“…Approximately 26% (N = 15) of the eligible studies examined remission among EoE patients who received only the diet elimination treatment formula (SFED, FFGED, ELED) compared to other forms of treatment, with the most common definitions falling within 0 to ≤5 eosinophils/hpf 29, 30, 31, 32, 33, 34 or 11 to ≤15 eosinophils/hpf 35, 36, 37, 38, 39, 40. Interestingly, even among the SFED studies (N = 9), five studies defined remission within the range of 0 to ≤5 eosinophils/hpf, 29, 30, 31, 32, 34 and two studies considered histological remission as <15 eosinophils/hpf 38, 41…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 26% (N = 15) of the eligible studies examined remission among EoE patients who received only the diet elimination treatment formula (SFED, FFGED, ELED) compared to other forms of treatment, with the most common definitions falling within 0 to ≤5 eosinophils/hpf 29, 30, 31, 32, 33, 34 or 11 to ≤15 eosinophils/hpf 35, 36, 37, 38, 39, 40. Interestingly, even among the SFED studies (N = 9), five studies defined remission within the range of 0 to ≤5 eosinophils/hpf, 29, 30, 31, 32, 34 and two studies considered histological remission as <15 eosinophils/hpf 38, 41…”
Section: Resultsmentioning
confidence: 99%
“…Six studies were published from centers in the United States, and the definitions provided include ≤5, ≤ 10, and ≤ 15 eosinophils/hpf. Notably, practically similar treatment options were used in the management of EoE subjects at the center 31, 34, 40, 41, 51. Two studies published from another US center, although with different treatment options and study design, used two different criteria to define histological remission 26, 52…”
Section: Resultsmentioning
confidence: 99%
“…A third strategy, empiric elimination, continues to grow in popularity. Kagalwala et al showed that eliminating the six most common allergenic food groups in the US (6-food elimination diet [SFED], consisting of milk, egg, soy, wheat, peanut/tree nuts, and seafood), without allergy testing, resulted in similar rates of symptomatic and histologic remission to an elemental diet control group (74 % response for SFED versus 88 % response in the elemental control group) [14,37].…”
Section: New Insights Into Dietary Therapy: Flexible Options Exist Almentioning
confidence: 99%
“…In 2006, Kagawalla et al excluded cows' milk protein, soy, wheat, eggs, peanuts and seafood from a cohort of 35 pediatric EoE patients, achieving a treatment efficacy of 74% after 6 weeks [78]. In a similar study, sequential food reintroduction with endoscopic and biopsy monitoring led to the identification of specific food triggers in pediatric EoE patients [79]. This strategy has also been used in adult patients with similar efficacy in achieving EoE remission in three out of four patients [80,81].…”
Section: Dietary Therapiesmentioning
confidence: 99%
“…Only by this method can offending foods be identified and definitively restricted from a patient's diet. Cows' milk has been identified as the most frequent cause of EoE in both children and adults, causing disease recurrence in approximately 70% of patients 6 weeks after being reintroduced in the diet [79][80][81], followed by wheat and eggs. North American and Spanish studies on six-food elimination diets have differed, with the latter excluding additional foods.…”
Section: Dietary Therapiesmentioning
confidence: 99%